2008
DOI: 10.2174/1874421400802010055
|View full text |Cite
|
Sign up to set email alerts
|

Desynchronizing Plasmodium Cell Cycle Increases Chloroquine Protection at Suboptimal Doses

Abstract: We have previously shown that in vivo and in vitro the hormone melatonin is responsible for the synchronous development of Plasmodia. Melatonin can also mobilize calcium from internal stores in these parasites and this response is abolished by luzindole, a melatonin antagonist. We here demonstrate that in vivo alteration of parasite synchronous development, using luzindole, partially improves survival of infected mice and dramatically increases the antimalarial activity of chloroquine. The data presented may l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 40 publications
0
9
0
2
Order By: Relevance
“…This antagonist has been used by several researchers to show the effect of melatonin, for instance describing the blockage of dopamine release in rabbit retina [94]. Luzindole has been described as abolishing the action of melatonin on Plasmodium [32,68,95,96]. However, it is still unknown whether the Plasmodium melatonin receptor works through a GPCR signaling mechanism.…”
Section: Melatonin Blockers As Potential Antimalarial Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…This antagonist has been used by several researchers to show the effect of melatonin, for instance describing the blockage of dopamine release in rabbit retina [94]. Luzindole has been described as abolishing the action of melatonin on Plasmodium [32,68,95,96]. However, it is still unknown whether the Plasmodium melatonin receptor works through a GPCR signaling mechanism.…”
Section: Melatonin Blockers As Potential Antimalarial Drugsmentioning
confidence: 99%
“…In addition, it was shown that when parasites lose synchronicity the protection provided by classical antimalarial drugs is enhanced at suboptimal doses [95]. These represent new avenues of research for the development of new combinations of pharmacologic drugs against malaria.…”
Section: Melatonin Blockers As Potential Antimalarial Drugsmentioning
confidence: 99%
“…When P. chabaudi infects pinealectomized mice, which lack melatonin, synchrony is lost but melatonin administration is able to restore it; this effect of melatonin is inhibited by the addition of luzindole (a melatonin antagonist) [19]. Administration of a suboptimal concentration of the anti-malarial drug, chloroquine in addition to luzindole reduces significantly the mortality of mice infected with P. chabaudi [32]. …”
Section: Receptors: the Upstream Part Of Signaling Pathwaysmentioning
confidence: 99%
“…A dessincronização dos parasitas em camundongos pinealectomizados pode ser revertida com a administração de melatonina (Hotta et al, 2000). Além disso, Bagnaresi et al (2008) demonstraram que quando camundongos infectados com parasitas P. chabaudi são expostos a luzindol, um antagonista de receptores de melatonina e agente dessincronizador das fases intraeritrocíticas (Hotta et al, 2000) há um aumento da sobrevida desses camundongos tratados com doses subótimas de cloroquina. Esses dados sugerem uma vantagem adaptativa da sincronicidade.…”
Section: Compostos Derivados Do Triptofano Modulam O Ciclo De Vida Deunclassified